Kimi ni todoke = From me to you. Soulmate. 1 - Shiina, Karuho (Kimi ni todoke, from me to you soulmate, 2024)
The story of Kimi ni Todoke continues in this sequel starring Sawako and her former rival Kurumi in college. With her jet-black hair, sinister smile, and silent demeanor, Sawako "Sadako" Kuronuma always had trouble fitting in during high school. But with help from her friends, her boyfriend Kazehaya, and even her rival-turned-friend Kurumi, Sawako came out of her shell. Now in college, Sawako and Kurumi have become incredibly close, but Kurumi longs for a romance of her own. In college, Kurumi thinks she's found her soulmate in Sawako, her rival-turned-best-friend from high school. But Kurumi can't help wondering if maybe there's someone else out there for her, despite her troubling track record with dating. When the opportunity to attend a mixer crops up, Kurumi drags Sawako along, setting in motion a dangerous love story...